IMPROVING WRITING SKILLS OF CHILDREN AT SEKAR PENGHARAPAN ORPHANAGE THROUGH PEN PALS - Ni Luh Warini; Ni Made Diana Erfiani; Putu Chrisma Dewi (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTSekar Pengharapan Orphanage is located on Jalan Veteran, Buduk, Mengwi, Badung, Bali. There were problems faced by children in the Sekar Pengharapan Orphanage related to problems of writing letters in English because of difficulties in understanding of grammatical structures in English and the structure of letters. This project was aimed to improve the ability to write children's letters in Sekar Pengarapan orphanage related to grammatical structures in English and correct letter structures. Improving the ability to write letters was done through the teaching process using pen pals. The method used was interviewed, teaching with pen pals to children, and also giving pretest and posttest. The result that the children have been able to improve their ability to write letters in English. This was seen from the results of the pretest and posttest which have increased. There was a percentage increase from the pretest to posttest result of 19.4%. Moreover, there was output in the form of handbooks to help children understand English letters and grammar well.Keywords: writing, improving, grammar, structure, and pen pals.